Can the stock market anticipate future operating performance? Evidence from equity rights issues - Kabir, Rezaul; Roosenboom, Peter (Journal of Corporate Finance, 2003)
This paper examines whether the stock market valuation impact is consistent with subsequent operating performance of firms. We use data for equity rights offerings—the widely adopted flotation method in the Netherlands. We first examine the stock market announcement effect of rights issues and observe that a statistically significant stock price decline takes place when companies announce rights issues. Further stock price decline is also observed during the subscription period. We then analyze post-rights issue operating performance of firms and find that, consistent with the announcement period decline in stock price, rights issuing firms subsequently exhibit a statistically significant decline in their operating performance. Additional investigation of both stock and operating performance declines provides full support for the information asymmetry hypothesis, partial support for the free cash flow hypothesis but no support for the window of opportunity hypothesis.